STIMULATION OF COOPERATION OF SMALL, MEDIUM AND LARGE INNOVATIVE BUSINESS IN FOREIGN COUNTRIES - A. Kirillov (Вестник университета)
The article is devoted to an assessment of abilities to integrate small, medium and large innovative business abroad. Experience of development of subcontracting and clusters in developed and developing countries is estimated. The role of the state support in questions of cooperation of small and large business in the innovative system is estimated.